2020
DOI: 10.1002/smll.201905875
|View full text |Cite
|
Sign up to set email alerts
|

Anionic Redox Chemistry as a Clue for Understanding the Structural Behavior in Layered Cathode Materials

Abstract: The anionic redox chemistries of layered cathode materials have been in focus recently due to an intriguing phenomenon that cannot be described by the number of electrons of transition metal ions. However, even though several studies have investigated the anionic redox chemistry of layered materials in terms of the charge compensation, the relationship between the origin of the structural behavior and anionic redox chemistry in layered materials remains poorly understood. In addition, a simultaneous redox proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…Different from the typical LiTMO 2 system where the extra electrons are the result of the steadied TM-O bond, the layered Li 2 MnO 3 crystal phase in the LRM oxide electrode materials makes it likely to extract additional electrons from the nonbonding O situation without triggered crystal structural degradation. Recently, experimental results indicated that the LOR chemistry is connected with the anisotropic structural feature of the layered electrode materials, albeit without offering the extra capacities beyond the theoretical specific capacities, as provided by Lee and co-workers . Consequently, these as-mentioned findings can present an influential horizon to the evolution of the high-energy-density electrode materials by facilitating an in-depth understanding on the TM oxidation–reduction chemistry and expanding the vision field of the LOR chemistry that has hitherto concentrated on the enhancement in material capacities of materials.…”
Section: Lattice Oxygen Redox Reaction Mechanisms Of Li-rich Mn-based...mentioning
confidence: 98%
“…Different from the typical LiTMO 2 system where the extra electrons are the result of the steadied TM-O bond, the layered Li 2 MnO 3 crystal phase in the LRM oxide electrode materials makes it likely to extract additional electrons from the nonbonding O situation without triggered crystal structural degradation. Recently, experimental results indicated that the LOR chemistry is connected with the anisotropic structural feature of the layered electrode materials, albeit without offering the extra capacities beyond the theoretical specific capacities, as provided by Lee and co-workers . Consequently, these as-mentioned findings can present an influential horizon to the evolution of the high-energy-density electrode materials by facilitating an in-depth understanding on the TM oxidation–reduction chemistry and expanding the vision field of the LOR chemistry that has hitherto concentrated on the enhancement in material capacities of materials.…”
Section: Lattice Oxygen Redox Reaction Mechanisms Of Li-rich Mn-based...mentioning
confidence: 98%
“…The normalized integrated intensity in the hybridized state of TM 3d and O 2p region. Reproduced with permission from Ref [63]. Copyright 2020, WILEY‐VCH.…”
Section: Basic Mechanism Of Interface Structure Degradationmentioning
confidence: 99%
“…studied the relationship between the origin of the structural behavior and anionic redox chemistry in layered materials. [ 63 ] According to O K‐edge XAS spectra, the results indicated the anionic redox chemistry was related to the anisotropic structural behavior of the layered cathode materials. Yan et al .…”
Section: Basic Mechanism Of Interface Structure Degradationmentioning
confidence: 99%
“…), leading to difficult situations in the (de)insertion of alkali-ions. 36,[171][172][173][174][175][176] Therefore, controlling the transition metal ions in the alkali-ion layer is one of the key Refs. 182,183 With permission of NPG.…”
Section: Defects and Channelsmentioning
confidence: 99%